Ethanolic Extract of the Fungus Trichoderma asperelloides Induces Ultrastructural Effects and Death on Leishmania amazonensis - Lopes, Danielle de Sousa; Santos, Uener Ribeiro dos; Dos Anjos, Danielle Oliveira; Silva Júnior, Lauro José Caires da; Paula, Vanderlúcia Fonseca de; Vannier-Santos, Marcos André; Silva-Jardim, Izaltina; Castro-Gomes, Thiago; Pirovani, Carlos Priminho; Lima-Santos, Jane (Frontiers in Cellular and Infection Microbiology, 2020)
The Trichoderma genus comprises several species of fungi whose diversity of secondary metabolites represents a source of potential molecules with medical application. Because of increased pathogen resistance and to lower production costs, the search for new pharmacologically active molecules with potent activity against pathogens has become more intense. In the case of American Cutaneous Leishmaniasis this is even more evident duo to the toxicity of current available treatments and the difficulties inherent to its administration. We have previously shown that fungus from genus Trichoderma can be used for treat cerebral malaria in mice model and inhibit biofilm formation. In this work, we evaluated the effect of the ethanolic extract of Trichoderma asperelloides (Ext-Ta) and its fractions on promastigotes and amastigotes of Leishmania amazonensis, one of the species responsible for Leishmaniasis. Results have shown that Ext-Ta has leishmanicidal action on L. amazonensis parasites, and that its pharmacological activity concentrates in the low molecular weight fraction of T. asperelloides extract (LMWF). Ultrastructural analysis demonstrated morphological alterations in the mitochondria and the flagellar pocket of promastigotes, with an increase of structures similar to lipid bodies and acidocalcisomes, disorganization of microtubules and intense vacuolization of the cytoplasm when amastigotes were present. We suggest the possibly activity of fungi from the genus Trichoderma as a promising chemotherapeutic for the control of Leishmania infections.